2007
DOI: 10.1111/j.1600-0838.2007.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between PPARGC1A genotypes and endurance capacity in Chinese men?

Abstract: Our purpose was to determine the possible association between genotypes of three polymorphisms (Gly482Ser, Thr394Thr and A2962G) of the peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PPARGC1A) gene, on one hand, and both the pre- (baseline) and post-training levels of maximal (i.e., maximal oxygen uptake [VO2max]) and submaximal human endurance capacity (i.e., running economy [RE]). We studied 102 young males (physically active, non-athletes; age: 19+/-1 yrs) from Northern China (of Han … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
4
20
0
1
Order By: Relevance
“…is positive replication (i.e., a consistent association) strengthens the evidence for the in uence of the polymorphism on phenotype. However, even if the replication occurs in more than one population, it does not mean that the same association will be found in every population of the world 29 . In fact, associations found in a study are frequently not replicated in subsequent studies [30][31][32][33] .…”
Section: Genome-wide Studiesmentioning
confidence: 99%
“…is positive replication (i.e., a consistent association) strengthens the evidence for the in uence of the polymorphism on phenotype. However, even if the replication occurs in more than one population, it does not mean that the same association will be found in every population of the world 29 . In fact, associations found in a study are frequently not replicated in subsequent studies [30][31][32][33] .…”
Section: Genome-wide Studiesmentioning
confidence: 99%
“…For example, the endurance capacity before training [as assessed according to the maximal oxygen uptake (VO2 max)] is not associated with the Gly482Ser polymorphism in young Chinese men (13). Additionally, another study showed that changes in the VO2 max after 18 weeks of endurance training did not differ between Gly482 and Ser482 carriers in a young Chinese cohort (13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the endurance capacity before training [as assessed according to the maximal oxygen uptake (VO2 max)] is not associated with the Gly482Ser polymorphism in young Chinese men (13). Additionally, another study showed that changes in the VO2 max after 18 weeks of endurance training did not differ between Gly482 and Ser482 carriers in a young Chinese cohort (13). These results are in agreement with the findings of a molecular-level study showing that the expression of the PPARGC1A gene in skeletal muscle is similar between young Gly482 and Ser482 carriers, although the PPARGC1A expression is significantly reduced in elderly subjects with the Ser482 allele (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported an association between genotype and human aerobic capacity [1] . Therefore, SNPs can be used to powerful tools in the study of human sports.…”
Section: Introductionmentioning
confidence: 99%